Kebermanfaatan Institutional Repository Bagi Mahasiswa Semester Akhir di Universitas Muhammadiyah Gresik - Yoga Setya Perdana (Universitas Wijaya Kusuma Surabaya, 2022)
Research Purpose. The research conducted by the author aims to determine the usefulness of the Institutional Repository for Final Semester Students of the University of Muhammadiyah Gresik. Methods. This study uses a qualitative method, with the type of case study research on the Benefit of an Institutional Repository. The number of informants was as many as ten students using the purposive sampling technique. Data collection techniques are carried out by observation, Interview and Documentation. Data Analysis. The data analysis technique uses the concept of Miles and Huberman: Reduction, Presentation and Drawing Conclusions. Result and Discussion. The study results indicate that the usefulness of the Institutional repository for final semester students at the University of Muhammadiyah Gresik is more desirable. This can be seen from the aspects (1) the Collection of intellectual works that have been effective for users, (2) the Provision of Open Access that makes it easier for students, (3) The positive impact given on Institutions and users, (4) Rapid dissemination of information through promotions, (5) Digital storage is more attractive to users and (6) Repositories minimize plagiarism.Keywords: Repository, Usefulness, Open Access Libraries